Analysis of Uncertainty Factors of Rice Availability in Karawang Regency Using a Dynamic System Approach - Anditania Sari Dwi Putri; Annisa Indah Pratiwi; Annisa Nurizzati (International Journal of Management Science and Information Technology, 2026)
Karawang Regency serves as a crucial national granary, playing a vital role in supporting food security. This study analyzes how climate change, shifting agricultural land areas, productivity, and population growth impact rice availability. Additionally, it models simulations to maintain stable rice supplies using a system dynamics approach. The model was developed using Causal Loop Diagrams (CLD) and Stock Flow Diagrams (SFD), and subsequently validated through Mean Absolute Percentage Error (MAPE). The validation results showed MAPE values of 5.6% for rice production and 3.2% for rice consumption, indicating that the model is valid. Simulation results revealed that although rice production is projected to remain higher than consumption, rice availability is expected to decline until 2046. Scenario analysis demonstrated that increasing productivity has the greatest influence on improving rice availability. First scenario consisting of a productivity level of 8 tons/ha, an annual change in agricultural land area of 65 ha, a population growth rate of 0.5%, and a maximum temperature increase of 0.035°C is projected to produce approximately 539,959 tons of rice availability by 2046. The proposed model can serve as a decision support system for local governments in maintaining food security through simulation-based policy planning by incorporating the effects of flooding, paddy grain prices, rice prices, and rice distribution and supply chain dynamics.